2023
DOI: 10.3390/biology12091192
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450s-Involved Enhanced Metabolism Contributes to the High Level of Nicosulfuron Resistance in Digitaria sanguinalis from China

Xumiao Wang,
Wei Hu,
Yuxi Li
et al.

Abstract: Large crabgrass (Digitaria sanguinalis (L.) Scop.) is one of the major malignant grass weeds in Chinese maize (Zea mays L.) fields, and it has recently developed resistance to the acetolactate synthase (ALS)-inhibiting herbicide nicosulfuron. This study focused on a suspected nicosulfuron-resistant (R) population (LJ-01) of D. sanguinalis, collected from Lujiang County in Anhui Province, China, to explore the resistance level and potential resistance mechanism. Whole-plant dose–response testing confirmed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Cytochrome P450 monooxygenases (P450s) provide the molecular basis for herbicide-based weed management through differential gene expression of P450 families, considering the main enzymes involved in herbicide metabolism due to their functional diversity, substrate specificity, and catalytic versatility (Siminszky 2006, Dimaano andIwakami 2021). Recent studies revealed that NSF resistance in weed populations was mainly conferred by P450-mediated enhanced herbicide metabolism, not by target-gene mutation or overexpression (Wang et al 2023). ZmCYP81A9 could affect the NSF metabolism as a key member of the P450 family, and its sensitivity and expression level to NSF were higher than those of other members of P450 family (Liu et al 2015).…”
Section: Gene Expression Levelsmentioning
confidence: 99%
“…Cytochrome P450 monooxygenases (P450s) provide the molecular basis for herbicide-based weed management through differential gene expression of P450 families, considering the main enzymes involved in herbicide metabolism due to their functional diversity, substrate specificity, and catalytic versatility (Siminszky 2006, Dimaano andIwakami 2021). Recent studies revealed that NSF resistance in weed populations was mainly conferred by P450-mediated enhanced herbicide metabolism, not by target-gene mutation or overexpression (Wang et al 2023). ZmCYP81A9 could affect the NSF metabolism as a key member of the P450 family, and its sensitivity and expression level to NSF were higher than those of other members of P450 family (Liu et al 2015).…”
Section: Gene Expression Levelsmentioning
confidence: 99%